Pemberdayaan Penguatan Kelembagaan dalam Pengembangan Wisata Danau Tangkas Desa Tanjung Lanjut Kecamatan Sakernan Muaro Jambi - Parmadi; Haryadi; Junaidi; Siti Hodijah; Dwi Hastuti; Heriberta (WIDA Publishing, 2022)
The purpose of this community service in empowering institutional strengthening in the development of Tangkas Lake tourism, Tanjung Continue Village, Sakernan District, Muaro Jambi Regency is to improve the community's economy during the COVID-19 pandemic. Economic improvement is carried out by optimizing the potential of tourism objects through village-owned enterprises (BUMDes). BUMDes in this area are still very young and most of their activities have not been running and developing as they should. Only a small part of the potential of BUMDes in this area is managed and optimized. Community participation involved in BUMDes is still low and has not prioritized transparency. In the future, it is hoped that villagers will foster a sense of belonging and take an active role in the tourism village development process. That’s why institutional strengthening empowerment by optimizing BUMDes is important to be carried out.